CLES-ICT: a scale to measure ICT constructivist learning environments in Malaysia - Wong, Su Luan; Bakar, Ab Rahim; Lo, Yoon Mee; Mohd Ayub, Ahmad Fauzi (Elsevier, 2010)
The purpose of this study was to validate an instrument to explore students’ preferences toward the constructivist learning environments for a discrete ICT subject. The instrument was customized and modified from the Constructivist Learning Environment Survey (CLES) questionnaire. It included five components of constructivist learning: Personal Relevance, Uncertainty of ICT, Shared Control, Critical Voice and Student Negotiation. Data were gathered from 440 Malaysian secondary school students. Data analyses supported the instrument's internal consistency reliability, factor structure, discriminant validity and its ability to differentiate between ICT classrooms.